Polymeric carbon quantum dots as efficient chlorophyll sensor-analysis based on experimental and computational investigation - Nazri, Nur Afifah Ahmad; Azeman, Nur Hidayah; Bakar, Mohd Hafiz Abu; Mobarak, Nadhratun Naiim; Masran, Athiyah Sakinah; Zain, Ahmad Rifqi Md; Mahdi, Mohd Adzir; Saputro, Adhitya Gandaryus; Wung, Triati Dewi Kencana; Luo, Yunhan; A. Bakar, Ahmad Ashrif (Elsevier, 2024)
This report introduces a microfiber chlorophyll sensor based on polymeric amine functionalized carbon quantum dots (NCQD) using the surface plasmon resonance technique. The silver (Ag) thin film, followed by NCQD-polyvinyl alcohol composite film, was deposited on the tapered optical fiber. The characterization of surface morphologies of NCQD-PVA film using a field emission scanning electron microscope shows that the contact area with the analyte was well covered with Ag and NCQD-PVA. The experimental results show that the fiber optic SPR sensor can detect chlorophyll in the 0.01–2.0 ppm range with a high sensitivity response and a detection limit of 1.90 nm ppm−1 and 0.78 ppm, respectively. This study observed no significant interference among the other ionic species (Fe3+, NH4+, NO3–, NO2–, and PO4-) due to the electrostatic and π-π interactions between NCQD and chlorophyll. Results from density functional theory calculation also confirm that the interaction of the NCQD with chlorophyll existed, and the strongest interaction occurs between nitrogen at pyridine sites of the carbon core and the oxygen group of chlorophyll. The proposed NCQD/PVA optical fiber sensor exhibits good sensing performance and correlates well with the standard method (R2 = 0.9501), suggesting a suitable technology candidate for real-time environmental monitoring applications.